Flow analysis of steady state forward flow of aortic valve prostheses using Particle Image Velocimetry - Lenz Christopher; Borowski Finja; Oldenburg Jan; Brandt-Wunderlich Christoph; Stiehm Michael; Schmitz Klaus-Peter (Current Directions in Biomedical Engineering)
Transcatheter aortic valve replacement (TAVR) has become the standard therapy for aortic valve stenosis in patients with high surgical risk. Understanding the flow dynamics in TAVR is crucial for its evaluation and optimization. Experimental flow measurement by means of Particle Image Velocimetry (PIV) is increasingly applied alongside numerical analyses. This study introduces a novel test rig concept enabling the determination of velocity fields using Stereo-PIV under steady forward flow conditions through a TAVR during the peak systole matching the ISO 5840-1:2021 requirements. The experimental setup utilized an impeller pump to generate steady forward flow through a silicone aortic root model with implanted TAVR. A Stereo-PIV setup captured velocity fields in both ventricular inflow and aortic outflow regions. Test conditions were based on physiological flow rates determined from pulsatile measurements. Illumination of the added particles in the test fluid was achieved using an Nd:YAG laser. Fluorescent polystyrol particles (size: 50 μm) were used for flow visualization. Results showed characteristic flow patterns: a central jet flow entering the TAVR in the ventricular flow field. A jet flow directed towards the sinus side and a recirculation zone forming on the opposite side of the sinus could be detected in the aortic outflow. The width of the recirculation zone increases with distance from the TAVR. Maximum flow velocities were detected at 0.78 m/s for the ventricular flow field and 0.94 m/s for the aortic flow field. This study provides a comprehensive approach for fluid dynamic analysis of TAVR under steady flow conditions, offering insights into flow mechanics performance crucial for device optimization. Further investigations could enhance the PIV - measurement procedure by increasing both the spatial resolution and the tracer particle density within the acquired images for a comprehensive characterization of TAVR flow dynamics.